1957
DOI: 10.1017/s0025315400017161
|View full text |Cite
|
Sign up to set email alerts
|

The determination of ammonia and total ionic inorganic nitrogen in sea water

Abstract: (Text-figs. I and 2) 161 Combined inorganic nitrogen occurs in sea water principally as nitrate, nitrite and ammonium ions, the concentrations of which lie in the ranges I-600 mg N03--Njm3, 0'1-5°mg N02--Njm3 and 5-50 mg NH4LNjm3 respectively. Nitrogen occurring in any of these forms is readily assimilable by marine organisms, and its exhaustion in sea water is frequently a growthlimiting factor in the water. This paper describes a method for the determination of the total ionic inorganic nitrogen in sea wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1957
1957
1999
1999

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Ocean Mn nodules typically are brown-black and subsphericalbotroyoidal and consist of concentric layers of primarily Mn and iron oxide minerals. Other minerals commonly found in the nodules include: clay minerals, quartz, apatite, biotite, and feldspars (10). Most Mn nodules have formed around central nuclei that may be carbonate mineral fragments, pumice shards, animal remains, coral fragments, etc.…”
Section: Ocean Mn Nodulesmentioning
confidence: 99%
“…Ocean Mn nodules typically are brown-black and subsphericalbotroyoidal and consist of concentric layers of primarily Mn and iron oxide minerals. Other minerals commonly found in the nodules include: clay minerals, quartz, apatite, biotite, and feldspars (10). Most Mn nodules have formed around central nuclei that may be carbonate mineral fragments, pumice shards, animal remains, coral fragments, etc.…”
Section: Ocean Mn Nodulesmentioning
confidence: 99%
“…Ammonia was determined by the diffusion method of Riley and Sinsaheni ( 1957) ; chlorinity by titration of halides with silver nitrate ( American Public Health Association 1955) ; dissolved oxygen by the unmodified Winkler technique (American Public Health Association 1955); hydrogen-ion concentration with a Beckman Model G pH meter ; and phosphate by the colorimetric stannous chloride method (American Public Health Association 1955). Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Riley (1953) has suggested that distillation under reduced pressure would suppress the breakdown of organics and recommended colorimetric determination by the phenatehypochlorite method to produce indophenol blue. In a later paper Riley and Sinhaseni ( 1957) demonstrated the use of microdfision flasks to separate ammonia from sea water in the presence of a metaborate buf€er at 7OOC. A tedious feature of the above methods is the need to separate the ammonia by distillation.…”
Section: Ammoniamentioning
confidence: 99%